Gambaran Angka Kuman Total pada Gagang Pintu Fasilitas Pelayanan Kesehatan di Rumah dan Puskesmas X (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Health care facilities are places used for promotive, preventive, curative, and rehabilitative health services carried out by the government and the community. Calculating the germ count on door handles of healthcare facilities is very important, because patients are not aware that the door handles contain and transmit germs that cause infections. This study aims to determine the percentage of germ contamination on door handles of healthcare facilities at X Hospital and X Community Health Center. The type of research conducted is descriptive quantitative with an observational case report approach. This study is a frequency distribution in tabular form using a percentage formula. The number of samples used by the researchers was 8 samples, using 4 sampling points at the Hospital and 4 sampling points at the Community Health Center (Puskesmas): the Emergency Room, Main Door, Pharmacy Room, and Laboratory Room. Data collection by conducting laboratory tests on door handle swab samples was then examined using the ALT method. The results showed that the percentage of door handles that did not meet ALT standards was 3 samples (75%) at X Hospital. Meanwhile, on door handles at health facilities Puskesmas. The percentage of door handles at Puskesmas was obtained 4 samples (100%) at X Puskesmas. Door handles at health facilities do not meet the standards of the Republic of Indonesia's Minister of Health Decree No. 1204 / MENKES / SK / X / 2004, the decision Ho was accepted H1 was rejected.